How image and trust determine preference: The case of Kaskus, OLX, and Tokopedia - Shannen Bonfilio (Jurnal Ekonomi Perusahaan, 2022)
The influence of brand image and trust on purchasing behavior has been widely studied. However, there is still little that connects it to brand preferences, especially in the context of different e-commerce platforms. This study investigates the effect of brand image and trust on e-commerce website preferences on three platforms: community-based Kaskus, classified advertising OLX, and marketplace Tokopedia. For this reason, the author recruited 219 respondents aged 17-60 years with junior high school education and above who made one of the three e-commerce platforms their favorite shopping sites. Data analysis using linear regression and path analysis shows that brand image and brand trust directly affect Kaskus and Tokopedia. In OLX, only brand trust affects brand preference. In addition, the brand image also affects brand preference for Kaskus and Tokopedia, while OLX does not. There are indications that brand image and brand trust work in relative terms. Future research could examine this indication. Original Document | Turnitin Plagiarism Check